Evaluating the Impact of Atmospheric Depositions on Springtime Dinitrogen Fixation in the Cretan Sea (Eastern Mediterranean)—A Mesocosm Approach - Rahav, Eyal; Shun-Yan, Cheung; Cui, Guo; Liu, Hongbin; Tsagaraki, Tatiana M.; Giannakourou, Antonia; Tsiola, Anastasia; Psarra, Stella; Lagaria, Anna; Mulholland, Margaret R.; Stathopoulou, Eleni; Paraskevi, Pitta; et al. (Frontiers in Marine Science, 2016)
Large amounts of dust and atmospheric aerosols, originating from surrounding desert areas (e.g., Sahara and Middle East) are deposited annually on the surface of the Eastern Mediterranean Sea. These depositions can provide high amounts of micro (such as Fe, Zn, Co) and macro nutrients (such as P and N) to supplement nutrient-poor surface waters- that typically limit primary productivity and also dinitrogen (N2) fixation in many marine environments. Here, we studied the impact of the atmospheric deposition of dust and aerosols on N2 fixation in the Cretan Sea (Eastern Mediterranean Sea). Mixed polluted aerosols (hereafter A) and Saharan dust (hereafter SD) were added to nine mesocosms (3-m3 each) containing surface mixed layer seawater (~10 m), and N2 fixation was evaluated for 6 days during May 2012 (springtime). The addition of SD triggered a rapid (30 h) and robust (2-4 fold) increase in N2 fixation rates that remained high for 6 days and contributed 3-8% of the primary productivity. The A addition also resulted in higher N2 fixation rates compared to the unamended control mesocosms, although the responses were less profound (1.5-2 fold) and accounted for only 2-4% of the primary productivity. The microbial community responded differently to the two additions. Heterotrophic bacterial N2 fixers dominated the diazotroph community in A and the control mesocosms, while the non-filamentous cyanobacterial group Trichodesmium prevailed in the SD treatment (68% of all the operational taxonomic units, verified by qPCR analyses). Our results indicate that the aerosol source, its route prior to deposition, and its specific chemical composition, can alter the diazotrophic diversity and activity in the Eastern Mediterranean Sea and may thus impact both the N and C dynamics in this impoverished environment.